Effect of an acute exercise on early responses of iron and iron regulatory proteins in young female basketball players - Cichon, J.; Ostapiuk-Karolczuk, J.; Cieslicka, M.; Dziewiecka, H.; Marcinkiewicz, A.; Tafil-Klawe, M.; Basta, P.; Maciejewski, D.; Skarpanska-Stejnborn, A. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background The accumulation of physiological stress and the presence of inflammation disturb iron management in athletes during intense training. However, little is known about the mechanisms regulating iron levels in athletes during training periods with low training loads. In the current study, we analyzed the effect of an acute exercise on early responses of iron and iron regulatory proteins at the end of such training periods.